Births in Wild Black and Gold Howler Monkeys (Alouatta caraya) in Northern Argentina - Peker, Silvana Marina (2009)
Previous studies on births in nonhuman primates suggest that births are expected to occur at night to avoid predators. Here, we describe birth-related behaviors in wild black and gold howler monkeys, Alouatta caraya and address the various ideas proposed in the literature about the timing of births in group-living nonhuman primates. We collected data on females’ birth-related behaviors through continuous focal observations and scan samples. Focal observations on females giving birth were taken for the remainder of the day after noticing a female was in labor. We recorded behaviors and the spatial distribution of the whole group using scan samples taken every 10 min from sunrise to sunset the same day of birth. We recorded five births at the continuous forest (CF) over a 25 months period (January 2004–December 2004 and September 2005–September 2006) and two births in the fragmented forest (FF) over a 13 months period (September 2005–September 2006). From these, four births were during daylight (two at CF and two at FF) and three during the night at CF. Our descriptions of A. caraya births contribute to a growing data set on the timing of parturition in wild nonhuman primates and suggest that a clear pattern of nocturnal births is not universal across nonhuman primate species.